2008
DOI: 10.1155/2009/797159
|View full text |Cite
|
Sign up to set email alerts
|

Identifying MMORPG Bots: A Traffic Analysis Approach

Abstract: Massively multiplayer online role playing games (MMORPGs) have become extremely popular among network gamers. Despite their success, one of MMORPG's greatest challenges is the increasing use of game bots, that is, autoplaying game clients. The use of game bots is considered unsportsmanlike and is therefore forbidden. To keep games in order, game police, played by actual human players, often patrol game zones and question suspicious players. This practice, however, is labor-intensive and ineffective. To address… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
3
3
3

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 23 publications
0
35
0
2
Order By: Relevance
“…• Network traffic: One of only a few papers to address bot detection in games "Identifying MMORPG Bots: A Traffic Analysis Approach" by Chen et al [2006] suggests that a traffic-level detection system is possible. Bot-generated traffic differs from human-generated traffic with respect to the regularity of the release time of commands, the trend and magnitude of traffic bursts in multiple time scales, and the sensitivity of interaction to network responsiveness.…”
Section: Bot Detection and Counter-detection Methodsmentioning
confidence: 99%
“…• Network traffic: One of only a few papers to address bot detection in games "Identifying MMORPG Bots: A Traffic Analysis Approach" by Chen et al [2006] suggests that a traffic-level detection system is possible. Bot-generated traffic differs from human-generated traffic with respect to the regularity of the release time of commands, the trend and magnitude of traffic bursts in multiple time scales, and the sensitivity of interaction to network responsiveness.…”
Section: Bot Detection and Counter-detection Methodsmentioning
confidence: 99%
“…To maintain and keep interesting personalities and behaviors always online, we can encapsulate them in the forms of autonomous agents that follow certain behavior scripts to act similarly as, and in the interests of, the original users. Many of today's popular MMOGs are troubled by bots [6], which are autonomous agents that continuously act and mine the resources inside games. They are often banned by game companies due to their disruptions to gameplay balance and fairness (i.e., players would gain experience points or virtual money without actually playing).…”
Section: Design Of Plugmentioning
confidence: 99%
“…Chen et al [24] proposed a traffic analysis approach to identify MMORPG bots. By investigating the traffic generated by mainstream game bots and human players in Ragnarok Online (one of the most popular MMOGs), it is observed that the traffic is distinguishable by: (1) the regularity in the release time of client commands, (2) the trend and magnitude of traffic of traffic burstness in multiple time scales and (3) the sensitivity to network conditions.…”
Section: Means For Addressing Cheating By Exploiting Machine Intelligmentioning
confidence: 99%